The quest for more food - Kelly, S (American Association for the Advancement of Science, 2022)
Enhancing photosynthesis is regarded as one of the most promising avenues for increasing crop yield (1). Accordingly, substantial focus has been drawn to this challenge, with several breakthroughs holding great potential (2). A common feature of these successes is that they have targeted metabolic processes, altering the rate and/or the path of metabolite flow through the plant to achieve higher rates of photosynthesis. However, on page 386 of this issue, Wei et al. (3) report an alternative approach. They show that photosynthesis and yield can be improved in rice by overexpressing a transcriptional regulator that promotes the expression of yield-associated genes. This highlights that there is a substantial latent capacity for enhancing photosynthesis hidden in the genomes of plants. Moreover, this latent capacity is present in abundance even in plants subjected to thousands of years of improvement through plant breeding.